Pengaruh Harga, Lokasi Dan Pelayanan Terhadap Loyalitas Konsumen Pada Jasa Laundry Happy Wash 21 Di Metro Lampung - Alintani, Zuhrotil Wasilah; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of price, location and service on consumer loyalty. The type of research used in this research is quantitative research. The object of this research is the Laundry Happy Wash 21 service which is located on Jalan Tengger No. 11 Yosorejo Metro Timur, Metro City, Lampung. The total population is 65 respondents. Data collection techniques using SPSS 25 and 20 include test instrument requirements, test requirements analysis, hypothesis testing. Based on the results of the study, it shows that the price variable has no and no significant effect on consumer loyalty, the location variable has an effect and is significant on consumer loyalty, and the service variable has no and no significant effect on consumer loyalty. Meanwhile, the simultaneous test of price, location and service has a significant and significant effect on consumer loyalty.